Little town on the prairie - Wilder, Laura Ingalls, 1867-1957. (Little house, 1971)
Pa's homestead thrives, Laura gets her first job in town, blackbirds eat the corn and oats crops, Mary goes to college, and Laura gets into trouble at school, but becomes a certified school teacher.